EFFECT OF GLYMIN, A POLYHERBAL FORMULATION ON LIPID PROFILE AND HISTOPATHOLOGICAL EXAMINATION IN STREPTOZOTOCIN-INDUCED DIABETIC RATS (International Journal of Pharmaceutical Sciences and Drug Research, 2012)
Diabetes Mellitus is a chronic widely spread human disease. Streptozotocin-induced diabetes in rats had been shown to be associated with functional and morphological changes in liver and kidney. This study was undertaken to investigate the effect of glymin on lipid profile and histopathological study of liver and kidney in streptozotocin-induced diabetic rats. Lipid profiles were investigated in serum and tissues (liver and kidney) of normal and streptozotocin-induced diabetic rats treated with glymin (50 and 100 mg/kg/day) for the period of 35 days. Diabetic rats exhibited an increase in the levels of total cholesterol, triglycerides, free fatty acids, phospholipids and low density lipoprotein cholesterol (LDL-cholesterol), and a decrease in the level of high density lipoprotein cholesterol (HDL-cholesterol). The administration of glymin shows decreased levels of total cholesterol, triglycerides, free fatty acids, phospholipids and LDL-cholesterol, and an increased level of HDL-cholesterol. The findings of this study indicate that the administration of glymin resulted in a better lipid profile which helps to recover the pathological effects of diabetes on liver and kidney of streptozotocin-induced diabetic rats.